Implications of the Sociology of Emotions for the Restoration of Social Order - Srbljinović, Armano (Array, 2014)
This article offers a conceptual analysis of the implications of the sociology of emotions for the restoration of social order in failing states. The authors mainly draw on ritual theories of emotions, but also use insights from dramaturgical, power and status, and exchange theories. It is argued that social order emerges from interactions among human individuals developing and internalizing emotional beliefs about their place within a wider social environment in the form of a social contract. Examples from states such as Afghanistan and Somalia illustrate the authors’ thesis that macro-level restoration of order is possible through change agents’ efforts at restoration of emotion-generating interaction ritual chains.